THE EXAMINATION OF THE EFFECTS OF THE RHYTHMIC TEACHING OF PHYSICAL EDUCATION ON SPEED OF 9-10 YEARS OLD GIRLS - Dragana Aleksić; Slađana Stanković; Vesko Milenković; Ljubiša Lilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
By different moving activities, learning about their body and its mothoric, a child develops its mothoric, acquires different motoric skills and habits and develops motoric activities. In this work, the subject of the research is just one segment of the anthropological area which refers to the appearance of appropriate motor abilities-speed. The research involved a total sample of 99 girls from the 3th and 4th grade of elementary school. The subjects were classified in experimental and control groups. The experimental group was made of 51 students and they were practicing according to planning instruction where the rhythmic gymnastics had the primary part. The control group of 48 students was practicing according to official instructional plan and program for P.E. of the Republic of Serbia. At the beginning of the academic year, initial (first) measurement was performed, followed by experimental final (second) measurement at the end of experiment. Research data was processed using SPSS standard statistics procedure. The multi-variant procedures were used in this research ant those were: the multi-variant analysis of the variable MANCOVA i MANOVA. Also, the mono-variant procedures were used and those were: the variable analysis ANCOVA, ANOVA and the interval of entrust. Considering the difference of the influence of the treatment, it can be pointed out that the experimental program, with all its characteristics, widely contributed to all its segments to the improvement of speed. It is known that the use of physical exercise stimulation only within regular physical education classes is not sufficient to provoke essential improvement of motoric abilities. Therefore it is very important not only to try to animate schoolboys for participation in additional sporting activities, especial rhythmic gymnastics, out of regular physical education classes, but, what is even more important, to increase the number of physical education classes a week, with the ambition to provide sufficient stimulation to ensure a harmonic somatic growth and development.